Community across Time : Robert Morgan's Words for Home - Godwin, Rebecca, 1954- (Book collections on Project MUSE., 2023)
"Considers the Appalachian writer Robert Morgan's explorations of memory, family history, and landscape. Provides a study of all of Morgan's fiction to date, as well as a chapter on his poetry and some reference, where appropriate, to his nonfiction. Examines the family history that informs much of this body of work, offering an extended biographical essay that ties characters and plot details to Morgan's ancestors' lives and to his own experiences growing up in the Blue Ridge Mountains"--